Programa de atención e intervención psicosocial orientado a la construcción de habilidades psicosociales para la vida desde la gestión del riesgo frente al embarazo en adolescentes de grado 9 en el colegio Carlos Federici (2021)
According to the Colombian Ministry of Health, "sexual health in adolescents is a public health problem with different social and economic consequences." According to the above, the risk factors that most affect pregnancy at an early age and the practice of unsafe sexuality in adolescents are: the intergenerational reproduction of poverty, low school achievement, lack of opportunities and lack of education. sex in institutions